Long-Term Outcomes of Minor Troponin Elevations in the Intensive Care Unit. Issue 3 (May 2014) - Velasquez, A.; Ghassemi, M.; Szolovits, P.; Park, S.; Osorio, J.; Dejam, A.; Celi, L.
The aim of our study is to determine the short-term and long-term outcomes of intensive care unit (ICU) patients with minor troponin elevations. The retrospective study compared ICU patients with peak troponin elevation less than 0.1 ng/ml to those with only negative tests during their hospital stay. Data were gathered from ICUs at Beth Israel Deaconess Medical Center between 2001 and 2008. A total of 4224 patients (2547 controls and 1677 positives) were analysed. The primary outcome was mortality at one year. Secondary outcomes were 30-day mortality and hospital and ICU lengths of stay. After adjusting for age, sex, Simplified Acute Physiology Score, Sequential Organ Failure Assessment and combined Elixhauser score, we found that minor troponin elevations (peak troponin elevation between 0.01 and 0.09 ng/ml) were associated with a higher one-year mortality (Hazard Ratio 1.22, P <0.001 for binary troponin presence; Hazard Ratio 1.03, P <0.001 for each 0.01 ng/ml troponin increment). This relationship held for the subgroup of seven-day post-discharge survivors (Hazard Ratio 1.26, P <0.001). Minor elevations of troponin also significantly increased the net reclassification index over traditional risk markers for mortality prediction (net reclassification score 0.12, P <0.001). Minor troponin elevation was also associated with 30-day mortality (odds ratio 1.33, P =0.003). Importantly, troponin testing did not increase the adjusted mortality odds ( P =0.9). Minor elevations in troponin substantially increase one-year, all-cause mortality in a stepwise fashion; it was also independently associated with 30-day mortality. We propose that minor elevations in troponin should not be regarded as clinically unimportant, but rather be included as a prognostic element if measured. We recommend prospective ICU studies to assess prognostic value of routine troponin determination.